2:1 ketogenic diet and low-glycemic-index diet for the treatment of chronic and episodic migraine: a single-center real-life retrospective study - Yan Tereshko; Simone Dal Bello; Cherubino Di Lorenzo; Sara Pez; Alice Pittino; Roberto Sartor; Francesca Filippi; Christian Lettieri; Enrico Belgrado; Riccardo Garbo; Giovanni Merlino; Gian Luigi Gigli; et al. (The Journal of Headache and Pain, 2023)
Abstract Aims The evidence supporting the efficacy of dietary preventive therapy in migraine is rising, particularly regarding the ketogenic diet. However, less evidence exists for the Low-Glycemic Index Diet and the 2:1 KD. This retrospective single-center real-life study aims to evaluate the efficacy of a 2:1 ketogenic diet and a Low-Glycemic-index Diet in chronic and high-frequency episodic migraine. Methods Sixty patients with high-frequency episodic and chronic migraine were treated with either a Low-Glycemic-index diet (39 patients) or a 2:1 (21 patients) ketogenic diet for three months. We collected data on the migraine frequency and intensity and the MIDAS and HIT-6 scores through the headache diary. Anthropometric measurements (BMI, fat mass, free fat mass, and weight) were also collected and analyzed similarly. Data obtained at the baseline and after three months of each diet were compared. Results Migraine intensity, frequency, MIDAS and HIT-6 scores, fat mass, weight, and BMI improved in both diet groups. Conclusions Both diets are effective in reducing migraine symptoms and migraine-related disability.